Challenge and coping strategies of financially-challeged mothers of children with autism spectrum disorder - Magalona, Maria Theresa G.; Agustin, Estrella R.; Sta. Maria, Maxine Camela S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT This study sought to give clarity to the situation of mothers of children with Autism Spectrum Disorder (ASD) who are financially-challenged. Thus, the study targeted 30 mothers with children, aged 6 to 11 years old with ASD who were enrolled in a school or center. The following aspects of their situation were explored: 1) the relationship between mother and child with ASD; 2) the challenges of having a child with ASD; and 3) the coping strategies utilized by the mothers. The research study employed qualitative data collection through individual interviews that obtained experiences and perceptions of 30 mother-participants on the given aspects. The similar responses were grouped together under themes for analysis. For the aspect on mother-child relations, the activities with their child with ASD, mother-participants? roles and responsibilities and their psychological aspect (e.g. fears, changes, motivations) were influenced by the child?s condition. These in turn have influenced the mothers? treatment or behavior towards the child, as seen in their role of assisting the child in self-help and pre-academic skills, providing the child with special education and therapy, and more. For the aspect on challenges and coping strategies, similar themes emerged among the responses of the mother-participants. These themes involved four areas: (1) childcare and management, (2) relationships (3) finance and (4) personal well-being. All themes highlighted the influence of the child?s special needs. The consistency among themes inferred how the mother-participants were proactive in addressing their situation. The most occurring theme was childcare and management, wherein the child?s condition was most manifested and directly dealt with. The research also contributes a list of coping strategies recommended by the mother-participants to aid mothers in need. Moreover, future researches on the experiences of fathers and siblings of children with ASD are suggested to increase awareness and knowledge on the family dynamics of children with ASD.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Mothers of autistic children -- Philippines; Mother and child -- Philippines